Attitudes toward caring for terminally ill patients among community nurses in Shanghai: A cross-sectional study - Yifei Xie; Tingting Cai; Aiyong Zhu; Xian Zhang; Chunjian Xu; Lijuan Song (International Journal of Nursing Sciences, 2025)
Objectives: This study aimed to evaluate attitudes toward caring for terminally ill patients and identify the associated factors among community nurses in Shanghai. Methods: The study was conducted among community nurses using convenience sampling in Shanghai between August and November 2023. The demographic questionnaire, the Frommelt Attitude Toward Care of the Dying Scale-B (FATCOD-B), and the Coping with Death Scale (CDS) were used for data collection. Data analysis was conducted using independent sample t-test, one-way analysis of variance, and multiple linear regression analysis. Results: A total of 1,396 community nurses participated in this study. The overall FATCOD-B score among community nurses was 102.27 ± 10.23, the attitude toward caring for the dying person’s family dimension scored the highest (4.03 ± 0.53), whereas the attitude toward the communication dimension scored the lowest (2.86 ± 0.52). The overall CDS score was 130.78 ± 20.25. Multiple linear regression analysis showed that death coping ability and blended death education accounted for 13.7 % of the variance in community nurses’ attitudes toward caring for terminally ill patients. Conclusions: Community nurses in Shanghai exhibit moderate attitudes toward caring for terminally ill patients. Nurses with greater death coping ability and those who participated in blended death education tended to have more positive attitudes toward terminally ill patients. These findings underscore the potential of blended death education as a practical strategy to enhance hospice care quality in community health service centers.